Pheochromocytoma presenting with severe abdominal pain and abnormal liver enzymes - Mhd Baraa Habib (11721774) (2023)
Pheochromocytoma can present with right hypochondrial pain, elevated liver enzymes, and a misleading appearance on ultrasound scan mimicking hepatic mass due to the proximity of adrenal masses to the liver. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4640